Estimation of above ground biomass and carbon of Pinus caribea in bulolo forest plantation, Papua New Guinea - Palpal, Timothy; Riwasino, John (Maderas. Ciencia y Tecnología, 2022)
Planted forest plays vital role in tree biomass which stored as carbon through carbon sequestration process and help reduce global warming and climate change effect. Estimation of biomass volume is the important process to determine the carbon contents stored in planted forest trees. Study was conducted to estimate the biomass and carbon content of Pinus caribea trees using allometry models at Bulolo forest plantation in Morobe Province of Papua New Guinea. Study involves center plot of the cluster design in order to collect field data as sample size The field data was collected by measuring stem of Pinus caribea tree species using two variables, diameter at breast height (DBH) and height. Finding reveals that first and highest rank biomass stem content and carbon stocking was 472,4 biomass/ha, followed by 407,076 biomass/ha and the least was 320,97 biomass/ha. Study reveals that biomass stem content and carbon stocking with 407,076 biomass/ha was the more suitable and applicable model for calculation of Pinus caribea in Bulolo forest plantation. Study recommends the log formula derived from the biomass stem content and carbon stocking of 407,076 biomass/ha, as the reliable model to be used for estimation of biomass content and carbon stock of Pinus caribea tree species Bulolo forest plantation and else way in Papua New Guinea.